2018
DOI: 10.1111/jmft.12339
|View full text |Cite
|
Sign up to set email alerts
|

Microaggressions and Islamophobia: Experiences of Muslims Across the United States and Clinical Implications

Abstract: This mixed methods exploratory study illustrates the influence of pervasive misconceptions about Islam on the experiences of 314 adult Muslims across the United States. Quantitative results suggest that Muslim stress levels are comparable to the stress levels of other marginalized groups in the United States. Qualitative analysis revealed four themes that highlight the challenges faced by Muslims as well as their resiliency in the face of microaggressions and marginalization. Family therapists may utilize thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 49 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…Recent interventions in social psychology point to the multifaceted nature of prejudice; from behaviors which are explicit, overt and direct to those which are implicit, covert and indirect (Nadal, Griffin, Hamit, Leon, & Rivera, 2012;Pettigrew & Meertens, 1995). Thus, in recent times much research has focused on 'everyday' prejudicial and hateful actions (Dunn & Hopkins, 2016;Moosavi, 2015) as well as 'micro-aggressions' (Haque, Tubbs, Kahumoku-Fessler, & Brown, 2018;Husain & Howard, 2017). Little research has explicitly explored these distinctions with regard to hate speech.…”
Section: Introductionmentioning
confidence: 99%
“…Recent interventions in social psychology point to the multifaceted nature of prejudice; from behaviors which are explicit, overt and direct to those which are implicit, covert and indirect (Nadal, Griffin, Hamit, Leon, & Rivera, 2012;Pettigrew & Meertens, 1995). Thus, in recent times much research has focused on 'everyday' prejudicial and hateful actions (Dunn & Hopkins, 2016;Moosavi, 2015) as well as 'micro-aggressions' (Haque, Tubbs, Kahumoku-Fessler, & Brown, 2018;Husain & Howard, 2017). Little research has explicitly explored these distinctions with regard to hate speech.…”
Section: Introductionmentioning
confidence: 99%
“…The usual target of this increased rejection are Muslim individuals, usually living in affected places. There are some papers that have found a link between Islamophobia and stress (Haque et al, 2019;Samari et al, 2018), which is particularly important for pregnant Muslim women as the evidence suggests that intra-uterine exposure to stress leads to detrimental health outcomes at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Islamophobia, with its discrimination and stigma, may be a source of stress that can negatively affect health (Samari, 2016). In fact, several studies have found a relation between Islamophobia and increased levels of stress (Haque, Tubbs, Kahumoku-Fessler, & Brown, 2019;Samari, Alcalá, & Sharif, 2018). This exposure to stress is particularly problematic for pregnant Muslim women who, in addition, are more easily identified as Muslims.…”
Section: Terrorist Attacks Islamophobia Stress and Health At Birthmentioning
confidence: 99%
“…Moreover, simultaneous to shifts and activism promoting social justice, there are moments that entrench inequality of various forms. For example, Islamophobia thrived in the immediate post-9/11 United States (Haque et al 2019). As another example, reported hate crimes against LGBT individuals surpassed previous high marks in recent years (Dashow 2017).…”
Section: Racism and Symbolic Empowermentmentioning
confidence: 99%